The Republic of Uzbekistan : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2013)
This report describes the results of an assessment of the accounting, financial reporting and auditing requirements and practices of the Republic of Uzbekistan's enterprise and financial sectors. The report uses, inter alia, International Accounting Standards (IAS), International Financial Reporting Standards (IFRS), and International Standards on Auditing (ISA) as benchmarks, and draws on international experience and good practices in the field of accounting and audit regulation, to assess the quality of Uzbek financial information and make policy recommendations